2023
DOI: 10.1021/acs.analchem.3c02687
|View full text |Cite
|
Sign up to set email alerts
|

Foldback-crRNA-Enhanced CRISPR/Cas13a System (FCECas13a) Enables Direct Detection of Ultrashort sncRNA

Yong Chen,
Yibin Zhang,
Siyuan Luo
et al.

Abstract: The CRISPR/Cas13a system has promising applications in clinical small noncoding RNA (sncRNA) detection because it is free from the interference of genomic DNA. However, detecting ultrashort sncRNAs (less than 20 nucleotides) has been challenging because the Cas13a nuclease requires longer crRNA− target RNA hybrids to be activated. Here, we report the development of a foldback-crRNA-enhanced CRISPR/Cas13a (FCECas13a) system that overcomes the limitations of the current CRISPR/Cas13a system in detecting ultrasho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Engineering crRNA modi cations has aimed at lowering detection thresholds 39,41 and improving SNP detection sensitivity 40,42 , focusing particularly on altering the DR sequence's stem-loop structure. Nguyen et al demonstrated the necessity of the stem region for Cas12a's functionality, in contrast to the dispensable loop region.…”
Section: Discussionmentioning
confidence: 99%
“…Engineering crRNA modi cations has aimed at lowering detection thresholds 39,41 and improving SNP detection sensitivity 40,42 , focusing particularly on altering the DR sequence's stem-loop structure. Nguyen et al demonstrated the necessity of the stem region for Cas12a's functionality, in contrast to the dispensable loop region.…”
Section: Discussionmentioning
confidence: 99%